Arithmetik elliptischer Kurven: 10.4. bis 16.4.1983 - Coates, John; Fröhlich, Albrecht; Roquette, Peter (Tagungsbericht, 1983)
D. Bernardi, Paris; B. J. Birch, Oxford; Gudrun Brattström, Orsay; J. Brinkhuis, Rotterdam; Bushnell, London; J. W. S. Cassels, Cambridge; J. Coates, Orsay; Volker Diekert, Hamburg; C. Deninger, Köln; M. Eichler, Arlesheim; Everest, London; G. Frey, Saarbrücken; A. Fröhlich, London; Ernst Gekeler, Bonn; W.-D. Geyer, Erlangen; R. Gillard, Grenoble; Catherine Goldstein, Orsay; F. Grunewald, Bonn; G. Harder, Bonn; D. Husemöller, Haverford; U. Jannsen, Regensburg; W. Jehne, Köln; E. Kani, Heidelberg; N. Klingen, Köln; M. Kneser, Göttingen; W. Kohnen, Bonn-Beuel; M. Laska, Bonn; H. W. Lenstra Jr., Amsterdam; S. Lichtenbaum, Orsay; B. H. Matzat, Karlsruhe; J. Mestre, Bordeaux; A. Néron, Orsay; J. Neukirch, Regensburg; J. Oesterlé, Paris; A. P. Ogg, Bonn; Olsen, Tromsø; B. Perrin-Riou, Paris; M. Rapoport, Heidelberg; J. Ritter, Augsburg; G. Robert, Grenoble; P. Roquette, Heidelberg; P. Satgé, Caen Cédex; Schappacher, Göttingen; C. Schmidt, Saarbrücken; P. Schneider, Regensburg; J. Tate, Cambridge; M. Taylor, Cambridge UK; R. J. Schoof, Leiden; J. Schwermer, Bonn; N. Stephens, Orsay; J. Tilouine, Orsay; St. Wilson, Durham; K. Wingberg, Regensburg; Jing Yu, Orsay; D. Zagier, Bonn; H. G. Zimmer, Saarbrücken
Text teilw. dt., teilw. engl
Keywords: Konferenzschrift